A mechatronic smart skin of flight vehicle structures for impact monitoring of light weight and low-power consumption. (October 2020) - Qiu, Lei; Lin, Xiaodong; Wang, Yu; Yuan, Shenfang; Shi, Wenli
Highlights: The MSS is a complete mechatronic system of light weight and low-power consumption. The MSS can acquire and process signals and record impact results by itself. The two-stage digitalization method can greatly reduce power consumption of the MSS. The ENS of the MSS can be easily implemented by a common FPC at a low cost. The weight and power consumption of the ENS are lower than 55 g/m 2 and 48 mW/m 2 . Abstract: This paper proposes a mechatronic smart skin (MSS) that has the ability to perform large-scale impact monitoring of flight vehicle structures with light weight and low-power consumption. The MSS is a complete mechatronic system that can acquire and process impact response signals and record impact results by itself. The MSS is achieved by integrating a large-scale flexible electronic network system (ENS) with a skin structure. The ENS is not just an ordinary piezoelectric sensor (referred as PZT) network but a complete impact monitoring network system, including a large-scale PZT network and a flexible impact monitoring system (FIMS) that is lightweight and exhibits low power consumption. The ENS can be easily manufactured by using a flexible printing circuit process that is commonly available at a low cost. In this paper, the principle and design of the MSS and the FIMS are first proposed. Then, an aircraft composite skin with several stiffeners is used as an example to achieve and validate a MSS. According to the validation results, the impact monitoring correctness of the MSS reaches 95%, and the additional weight and power consumption of the MSS introduced by the ENS are lower than 55 g/m 2 and 48 mW/m 2, respectively.